Hydrochemistry and geoaccumulation of metals in superficial sediments of the Laguna de Metztitlán, Hgo. Mexico. - Cruz-Sánchez, Misael; Avila-Ortiz, Anallely; Lobaco-Mejía, Violeta; Girón-García, Patricia; Salcedo-Luna, Cecilia (Tópicos de Investigación en Ciencias de la Tierra y Materiales, 2020)
The Metztitlán lagoon is a shallow natural reservoir that is part of the Barranca de Metztitlán Biosphere Reserve; it is a highly vulnerable system due to the incorporation of wastewater, as well as seasonal variations in rain-drought cycles. The physicochemical evaluation of a series of water samples and superficial sediments allowed classifying the nature of the water as lithotrophic with a Ca-Mg-HCO3 facie, C2S1 salinity, and an average permeability of 44.53% that make it suitable for irrigation. Sediment mineralogy is defined primarily by calcite, quartz, plagioclases, and kaolinite. The evaluation of the enrichment factor and the geoaccumulation index showed a moderate enrichment of V, Mn, Cu, Zn, and Pb in the sediments, as well as a positive geoaccumulation for V, Zn and Pb, indicating possible contamination with these metals.